Gastroprotective effect of freeze dried stripped snakehead fish (Channa striata Bloch.) aqueous extract against aspirin induced ulcerogenesis in pylorus ligated rats - Khan, Mohammed Safwan Ali; Mat Jais, Abdul Manan; Hussain, Javeed; Siddiqua, Faiza; Reddy, A. Gopala; Shivakumar, P.; Madhuri, D. (Hindawi Publishing Corporation, 2014)
Channa striata (Bloch.) is a fresh water fish belonging to the family Channidae. The stripped snakehead fish possesses wide range of medicinal properties. In view of traditional use of C. striata for wound healing, the present study was undertaken to investigate the beneficial effects of orally administered freeze dried aqueous extract of Channa striata (AECS) in experimentally induced gastric ulcers in Wistar rats. Aspirin induced ulcerogenesis in pyloric ligation model was used for the assessment of antiulcer activity and Ranitidine (50 mg/kg) was employed as the standard drug. The various gastric parameters like volume of gastric juice, pH, free and total acidities, ulcer index, and levels of antioxidant enzymes like catalase, superoxide dismutase, and lipid peroxidation marker malondialdehyde were determined. AECS at concentrations of 40% and 50% w/v significantly decreased the volume of gastric juice and increased the levels of catalase while considerable decrease in free and total acidities and increase in superoxide dismutase were observed with the treatment of standard drug and AECS (50% w/v). All the test doses of AECS markedly decreased ulcer index and malondialdehyde compared to the standard drug whereas AECS 30% w/v did not alter volume of gastric juice, pH, free and total acidities, catalase, and superoxide dismutase. From these findings, it can be concluded that AECS is devoid of acid neutralizing effects at lower doses and possesses antisecretory and antiulcer activities and this could be related to its antioxidant mechanism.